2018
DOI: 10.1016/j.hrtlng.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study of symptom perception in patients with chronic heart failure

Abstract: Many HF patients were poor at interpreting and managing their symptoms. These results suggest a subgroup of patients to target for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 64 publications
5
60
1
3
Order By: Relevance
“…The lack of action may be partially due to the HF symptoms not being clear indications of worsening HF to the patient, with symptoms interpreted as everyday symptoms or attributed to other chronic conditions. This is similar to previous research reporting poor HF symptom identification and response due to confusion over HF symptoms (Riegel et al., ; Zavertnik, ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The lack of action may be partially due to the HF symptoms not being clear indications of worsening HF to the patient, with symptoms interpreted as everyday symptoms or attributed to other chronic conditions. This is similar to previous research reporting poor HF symptom identification and response due to confusion over HF symptoms (Riegel et al., ; Zavertnik, ).…”
Section: Discussionsupporting
confidence: 92%
“…Vignette responses allowed us to examine HF patients' ability to interpret symptom changes and their plan for action. Our findings are consistent with reported challenges in HF symptom interpretation (Lee et al., ; Riegel et al., ) and add a new perspective in how clinicians or researchers could elicit HF patient symptom interpretations. Similar to our sample, previous studies have found that HF patients often seek help emergently when they have difficulty breathing (Altice & Madigan, ); however, the importance of seeking help with other HF symptoms (i.e., fatigue, weight gain and oedema) is less clear for HF patients (Clark et al., ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(İlerlemiş KY olan hastalarda konjestif semptomların azaltılması için sıvı alımı 1. . [1,[8][9][10][16][17][18][19][20][21][22] Pulmoner Ödem…”
Section: Hemşirelik Bakımıunclassified
“…Ayrıca çoğunun semptom algısının hemodinamik göstergeleriyle uyumlu olmadığı gösterilmekte tüm bunların sonucunda hastalar, çok daha ağır semptomlarla hastaneye başvurmaktadır. [21,22,25] Hasta eğitiminde hemşireler oldukça önemli rollere sahiptirler. Hasta eğitimi ile ilaç ve hastalık uyumları, daha önemlisi hayat kalitesi arttırılabilir, tekrarlı yatışlar azaltılabilir ve giderek artan bu yaygın hastalığın ekonomik yükü hafifletilebilir.…”
Section: Tedaviunclassified